New insight into the effect of hydroxyl substituted flavonoids on the cytotoxicity of 2‐amino‐3‐methylimidazo[4, 5‐f]quinoline. Issue 1 (31st December 2022) - Deng, Hongting; He, Yuanju; Cao, Hui; Chen, Lei; Teng, Hui
Abstract: The aim of the present work was to evaluate different structures of flavonoids interfering with the cytotoxicity of heterocyclic amines (HCA). Eight flavonoids with similar structure including myricetin, rutin, fisetin, quercetin, myricetrin, quercetrin, kaempferol, and galangin were coincubated with 2‐amino‐4‐methylimidazo[4, 5‐f]quinolone (IQ) respectively to determine the cytotoxicity. The results revealed that IQ at low doses showed no cytotoxicity; however, in the presence of myricetin and rutin, the cytotoxicity significantly elevated. It seems that C‐3′, C‐4′, C‐5′, and C‐5 hydroxyl substituents on the flavonoid skeleton of B ring play important role in the increasing cytotoxicity induced by IQ in HepG2 cells. Interestingly, the data obtained from the present study revealed an unexpected adverse effect of the supposed beneficial food ingredient myricetin, which appears to be able to increase the cytotoxicity of the procarcinogen HCA.